The grammar of words an introduction to linguistic morphology - Booij, G. E. (Oxford textbooks in linguistics., 2007)
"This is a basic introduction to how words are formed. It shows how the component parts of words affects their grammatical function, meaning, and sound"--Provided by publisher.